Carbene or C1 polymerization - De Bruin, B.; Chikkali, S.H. (Metal-catalyzed polymerization: fundamentals to applications, 2017)
As noted in Chapter 2, metal-catalyzed polymerization of carbon-carbon double bond (C=C) containing monomers is most widely known and today we produce roughly 180 million tons of polyolefins every year. 1 In this so-called olefin polymerization or vinyl insertion polymerization method, each monomer delivers two carbon (C2) atoms in each propagation step. Insertion polymerization of monomers delivering only one carbon unit in each chain growth step is named as C1 or carbene polymerization (see Figure 3.1). 2 In the recent past, C1 polymerization techniques are being viewed as a valuable alternative to the classical C2 polymerization methods. Not only this but also C1 polymerization offer distinct advantages over C2 polymerization and thus opens up new avenues for the development of new material with polymer properties that are very difficult to achieve using traditional C2 polymerization methods. In this chapter we will discuss the significance of C1 polymerization and the different methods used for C1 polymerization, will summarize the recent developments, and will highlight the elementary steps involved in it.